Biology of Prodiplosis longifila Gagné and population fluctuation in tomato crops sprayed with insecticides (2018)
Laboratory studies were carried out to determine life history parameters of the bud midge Prodiplosis longifila, a key pest of tomato. P. longifila eggs collected from tomato fields hatched into larvae within 1.2 days average and development time (larva I to adult) was around 14 days at environmental conditions. Sex ratio (male:female) of P. longifila was 1:1.03. Longevity of both male and female P. longifila adults (1.1 days for both of them) increased after sugar feeding. Field trials to determine population fluctuation of P. longifila were conducted in three commercial tomato plots located in Colombia, under calendar-based insecticide treatments. Average numbers of live P. longifila larvae in all plots were higher during the last two weeks of sampling than during the first two. Larvae numbers increased even under insecticide spraying. Larvae numbers increased after flowering, suggesting that adults were attracted to tomato flowers and probably used them as source of sugar. Infestation (%) was positively correlated with average number of larvae/leaf bud, suggesting the potential of this indirect method to monitor P. longifila larvae in tomato. Insecticide sprays, applied to tomato fields to control P. longifila, on a calendar-based regime, did not reduce larvae density.